Women and wars - Cohn, Carol (Cambridge, UK : Polity Press, 2013)
'Where are the women? In traditional historical and scholarly accounts of the making and fighting of wars, women are often nowhere to be seen. With few exceptions, war stories are told as if men were the only ones who plan, fight, are injured by, and negotiate ends to wars. As the pages of this book tell, though, those accounts are far from complete. Women can be found at every turn in the gendered phenomena of war. Women have participated in the making, fighting, and concluding of wars throughout history, and their participation is only increasing at the turn of the 21st century. Women experience war in multiple ways: as soldiers, as fighters, as civilians, as caregivers, as sex workers, as sexual slaves, refugees and internally displaced persons, as anti-war activists, as community peace-builders, and more. This book at once provides a glimpse into where women are in war, and gives readers the tools to understand women's (told and untold) war experiences in the greater context of the gendered nature of global social and political life'--P. [4] of cover.
Foreword / Cynthia Enloe -- Women and wars : toward a conceptual framework / Carol Cohn -- Women and the political economy of war / Angela Raven-Roberts -- Sexual violence and women's health in war / Pamela DeLargy -- Women forced to flee : refugees and internally displaced persons / Wenona Giles -- Women and political activism in the face of war and militarization / Carol Cohn, Ruth Jacobson -- Women and state military forces / Jennifer G. Mathers -- Women, girls, and non-state armed opposition groups / Dyan Mazurana -- Women and peace processes / Malathi de Alwis, Julie Mertus, Tazreena Sajjad -- Women, girls, and disarmament, demobilization and reintegration (DDR) / Dyan Mazurana, Linda Eckerbom Cole -- Women'after' wars / Ruth Jacobson.
Includes bibliographical references (p. 250-278) and index.
Keywords: Women and war